Visualization of Tourism Site Visit Levels in Karo Regency Using Tableau - Utama, I Made Putra; Putra, I Gede Ardi Sukaryadi; Sandhisutra , Ida Bagus Ketut; Mahendra, Gede Surya; Desmayani, Ni Made Mila Rosa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
Indonesia is one of the places with numerous tourist destinations and have unique attractions. One such province is North Sumatra, precisely in Karo Regency. However, to maximize the potential of tourism and achieve sustainable growth, a good understanding of tourist visitation rates to these attractions is essential. Timely, detailed, and integrated information on the number of tourist visits is crucial for formulating tourism policies, developing infrastructure, and effective resource management. The research objective is to develop a BI dashboard using Tableau software that can deliver information related to tourist visitation data in Karo Regency from 2010 to 2016 in an interactive and easily understandable manner. The study employed a secondary data analysis method by processing data collected from the Karo Regency government. The research process comprised data collection, data cleaning, Tableau implementation, and result analysis. Based on the conducted research, it can be concluded that during the period from 2010 to 2016, the tourist destinations with the highest number of visits were Lag Sibayak and Lau Debuk-Debuk, attracting a total of 1,099,738 tourists. On the other hand, Lag Sinabung, Danau Lau Kawar, and Gunung Sinabung were the tourist destinations with the lowest number of visits, with a total of only 52,282 tourists.